PERANCANGAN INSTRUMEN ASESMEN ADAPTIF PADA GAYA BELAJAR KOLB UNTUK MENINGKATKAN KEMAMPUAN COMPUTATIONAL THINKING SISWA - Krisna Milenia, - (2022)
To measure the success of the learning process, it is necessary to conduct an assessment of learning outcomes. The results of the assessment are not always good because there are still students who get scores below the KKM due to low problem solving abilities. However, these abilities are important so that students can improve competencies, so these abilities must be improved. In education, there is a problem-solving technique, namely Computational Thinking (CT). Previous research has improved the ability of CT using assessment instruments and in order to manage it properly, it is necessary to consider learning styles. This study aims to determine the improvement of students' CT abilities in database subjects after being given an adaptive assessment instrument. This research uses quantitative methods. The results of this study are: 1) Adaptive assessment instruments can improve students' database problem solving skills, especially for students with Assimilator learning styles with gains of 0.50 in the "medium" category and 0.77 convergers in the "high" category, the characteristics of the questions are appropriate. with this learning style, namely complex and simple analytical questions, problem-based questions packaged in a story/case, questions related to abstract concepts, questions to examine information, questions to generate ideas, and the cognitive domain given, namely C3 (applying). . 2) Adaptive assessment instruments can improve CT abilities even though the increase is low with the gain of all learning styles in the "low" category. 3) Student responses to the adaptive assessment instrument as many as 92.3% of students felt happy and challenged to work on the questions given and 83.3% wanted questions like that to be given during class learning. Based on the results of the study, it can be concluded that the adaptive assessment instrument can improve students' CT abilities, especially in the Assimilator and Converger learning styles.